Medical complications during a community-based mass participation endurance running event – an investigation of the epidemiology and risk factors associated with medical complications, with recommendations for risk mitigation - Schwabe, Karen (Department of Human Biology, 2021)
Background: The epidemiology and risk factors associated with medical complications, including life-threatening complications during distance running events has not been well described. The aims of this research were to document the incidence of medical complications (study 1), determine risk factors associated with medical complications (studies 2 and 3), and develop and apply a pre-race medical screening tool to determine the prevalence of chronic disease in race entrants, using a risk stratification model (study 4). Design: Prospective studies Setting: Two Oceans Marathon races (2008-2011) (studies 1-3) and race entrants (2012) Participants: Studies 1-3: 65 865 race starters; 21.1 km (n =39 511), 56 km runners (n=26 354). Study 4: 15 778 race entrants Methods: Study 1: In all 4 years, race day medical complications were recorded and subdivided by severity (serious life-threatening/death), organ system and final diagnosis. Studies 2 and 3: Independent risk factors associated with all medical complications, severity and organ system involvement were determined in 21.1 and 56km runners, using multivariate modeling. Study 4: A pre-race medical screening tool was developed, based on international pre-exercise medical screening guidelines, and administered to all race entrants (2012). The prevalence (%) of runners with four risk categories was determined. Results: The incidence (per 1000 race starters) of all and serious/life-threatening medical complications was 8.27 and 0.56 respectively (study 1). Risk factors associated with medical complications were less experience (56km), slower running pace (56 km) and older females (21.1 km) (studies 2 and 3). 16.8% runners were identified as those that should undergo medical evaluation for suspected cardiac disease with 3.4% reporting existing CVD (very high risk) and 13.4% reporting multiple CVD risk factors (high risk) (study 4). Conclusion: The incidence of all and serious/life-threatening medical complications in the 21.1km and 56km race is 1/121 and 1/1786 race starters respectively. Race experience, running pace and sex are risk factors for medical complications. 16.8% runners have underlying suspected cardiovascular disease. These data formed the basis for the implementation of a pre-race medical screening and risk stratification. The research lays the foundation for a future educational intervention programme to reduce the risk of medical complications in distance running and other endurance events.